2012
DOI: 10.1590/s0037-86822012000300013
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of Trypanosoma cruzi infection in the semiarid rural zone of the State of Rio Grande do Norte, Brazil

Abstract: INTRODUCTION: A seroepidemiological survey was carried out to evaluate Trypanosoma cruzi infection in an endemic area of the State of Rio Grande do Norte, Brazil, involving rural residents. METHODS: Sixteen municipalities were randomly selected, 15 from the west mesoregion and one from the central, with an estimated population of 83,852 individuals. A total of 1,950 blood samples were collected in the west mesoregion and 390 in Caicó. Anti-T. cruzi antibodies were detected using the Chagatest® ELISA HA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 30 publications
1
15
1
8
Order By: Relevance
“…More recent data support an estimated seroprevalence of 6.5% for chagasic infection in the Western mesoregion of RN, although that study did not examine the clinical forms of ChD (12) . Therefore, the present study aimed to characterize the different clinical forms of ChD, its evolution among seroreactive individuals from different municipalities in western RN, and its association with disease severity.…”
Section: Brazilmentioning
confidence: 89%
See 2 more Smart Citations
“…More recent data support an estimated seroprevalence of 6.5% for chagasic infection in the Western mesoregion of RN, although that study did not examine the clinical forms of ChD (12) . Therefore, the present study aimed to characterize the different clinical forms of ChD, its evolution among seroreactive individuals from different municipalities in western RN, and its association with disease severity.…”
Section: Brazilmentioning
confidence: 89%
“…The present study was performed in the West mesoregion, which covers >40% of RN's surface area (53,077.3km²) (Figure 1). This area was selected because a previous seroepidemiological survey was performed in this region during 2007-2009, and reported an estimated ChD prevalence of 6.5% (12) .…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…A recent seroepidemiological survey showed high seroprevalence for municipalities in the west and central mesoregions of the State of Rio Grande do Norte (RN) (28) , and genotyping studies identified T. cruzi I (TcI) in T. brasiliensis and TcIII (formerly called TcIIc) in armadillos (29) , TcI and TcII in humans, TcII and TcIII in T. brasiliensis, and TcIII in P. lutzi (15) .…”
Section: Methodsmentioning
confidence: 99%
“…About 90% of the territory represents arid and semiarid climates, where the predominant biome is the Caatinga, characterized as containing thorny shrubs, irregular structure, and partially uncovered soil. This study was conducted in the municipalities of Apodi, Caraúbas, Governador Dix-Sept Rosado, Lucrécia, Mossoró, Severiano Melo, São Miguel, Caicó, and Serra Negra do Norte in the West and Central mesoregions (Figure 1), which were selected in reference to the seroepidemiological survey conducted between 2007 and 2009 (28) .…”
Section: Study Areamentioning
confidence: 99%